Roots of death: origins of human burial and the research on Early Holocene mortuary practices in the Iberian Peninsula - Peyroteo-Stjerna, Rita (2018)
In the context of postglacial environmental changes, the new form of settlement known to exist in the Late Mesolithic seems to be followed by a different relationship to death. In the archaeological record, this is well observed in the shell midden sites known in both the Tagus and Sado valleys in Portugal, with ca. 374 human burials of both sexes and ages, mostly individual primary depositions. This concentration of human remains and the regular practice of funerary burial are in apparent contrast with the archaeological record for previous phases, at least in the Iberian Peninsula. Here, I present a review of the archaeological data available for the mortuary practices of the Early Holocene, i.e. Early Mesolithic, in the Iberian Peninsula, prior to these Late Mesolithic cemeteries in the Tagus and Sado valleys, and attempt to trace back in time the possible origins of this behaviour in the hunter-gatherer mortuary tradition.